The Development of Educational Aids for Restitution Coefficient Experiment Using Microcontroller - Indrasari, Widyaningrum; Budi, Agus Setyo; Fadilla, Dias Prima (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2022)
This study aims to produce a product in the form of high school physics teaching aids for collision materials. The aids developed consist of Arduino as the central controller, photodiode sensor, and infrared sensor as ball motion detector mounted on the side of the tube track as high as 100 cm. The aids can record the time and altitude automatically on the bouncing ball. The research method used is R&D development research with the ADDIE model, which includes five stages, analysis, design, development, implementation, and evaluation. The variables used are variations in the type of ball and the pedestal type. Three types of balls are used: ping pong, golf, and tennis. The base types are ceramic floor, stainless steel, and acrylic. The ball bounce is an elastic collision partly because it has a restitution coefficient value of 0 < e < 1. This experiment is done by ignoring air resistance and tracking friction. Students can make observations with the help of worksheets, which were also developed into the one-unit package. Through the validation test phase, the product has the worksheets get a value of 91% and the teaching aids 81%, which means that the worksheets and teaching aids are suitable for teaching materials to support learning physics.